Analysis of Circulations and Physical Variables in Multi-levels Associated with two Types of Regional Persistent Heavy Rainfall Events - Qin WANG; Bo ZENG (Gaoyuan qixiang, 2022)
Based on the precipitation data of meteorological stations in Sichuan Basin from 1961 to 2015 provided by Sichuan Meteorological Bureau and daily reanalysis data provided by NCEP / NCAR， the differences of large-scale circulations， source and transportation of water vapor， and physical environment conditions between regional persistent heavy rainfall events （RPHRs） in western and eastern Sichuan Basin in recent 55 years are analyzed.The results show that： （1） during the western basin events， the longitudinal development of the troughs and ridges in the mid-high latitudes are not as strong as that in eastern basin events.The Balkeshi Lake trough is located more west and north with the evolution of more stable and less moving， and then there are short-wave troughs splitting from it and moving southward to influence the western basin.However， the situation is quite different in the eastern basin events.As the Balkeshi Lake trough moves southeastward， it split into two troughs after entering China， so that the trough moved eastward along the Gansu and Shanxi provinces， and then developed in a southeastward direction to influence the eastern basin of Sichuan.（2） Compared with the eastern basin events， the South Asia high （SAH）， the West Pacific subtropical high （WPSH）， the high and low-level jet stream and the low-level cyclonic shear are located more northwest during the west basin events， and the intensity of these systems are relatively weaker.As the regions west of 130°E， the WPSH elongated meridionally in the western basin type， but in the eastern basin type， it is banded zonally.What’s more， the high level jet stream slopes southeastward.（3） Affected by the large-scale circulations， the dynamic characteristics of the upward movement along with low-level convergence and high-level divergence are more west in western basin events.The water vapor required by persistent rainstorms is mainly from Bay of Bengal and transported by the southwest airflow in western basin events， while that is from South China Sea and by southeast airflow in the eastern basin events， with stronger convective instability energy.（4） Compared with the climatological mean， there is a stable and less active "anticyclone-cyclone-anticyclone" circulation anomaly from the Lake Balkesh to Eastern China in the western basin events， while in the eastern basin events， the circulation anomaly shows a pattern of "anticyclone-cyclone-anticyclone-cyclone"， and during the rainstorm， the pattern developed in southwestward direction which is closely related to the more eastward and southward propagation of Rossby wave.